Binder for negative electrode sheet, secondary battery, and electronic device

CN120453383BActive Publication Date: 2026-11-03NINGDE AMPEREX TECHNOLOGY LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510599574.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-05-09
Publication Date
2026-11-03
Estimated Expiration
2045-05-09

AI Technical Summary

Technical Problem

In the prior art, during the charging and discharging process of secondary batteries, the reaction between the surface of the negative electrode active material and the electrolyte forms an SEI film, which hinders lithium-ion transport, affects cycle performance and kinetic performance, and increasing the amount of binder will worsen the kinetic performance.

Method used

A binder containing copolymers is used. The copolymers consist of a first monomer, a second monomer, a crosslinking monomer, and a functional monomer. By adjusting the phase angle boost rate and the phase angle, the binder is ensured to be uniformly attached to the surface of the negative electrode active material particles, thereby reducing the contact area and improving lithium-ion conductivity.

Benefits of technology

It effectively reduces the contact area between the surface of the negative electrode active material particles and the electrolyte, reduces side reactions, and improves the cycle performance and kinetic performance of the secondary battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120453383B_ABST
    Figure CN120453383B_ABST
Patent Text Reader

Abstract

The application provides a binder for a negative electrode sheet, a secondary battery and an electronic device. The binder comprises a copolymer, monomers forming the copolymer comprise a first monomer, a second monomer, a crosslinking monomer and a functional monomer, the first monomer comprises at least one of acrylic acid or methacrylic acid, the second monomer is selected from C7 to C 19 acrylate compounds, the functional monomer comprises at least one of allyl triethoxysilane, N-propyl triethoxysilane or 3-aminopropyl triethoxysilane; the phase angle improvement rate of the binder is α%, 25≤α≤75. The binder of the application has good affinity with negative active material particles, and the use of the binder of the application in the negative electrode sheet is conducive to improving the cycle performance and kinetic performance of the secondary battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of electrochemical technology, and in particular to a binder for negative electrode sheets, a secondary battery, and an electronic device. Background Technology

[0002] Secondary batteries, such as lithium-ion batteries, have advantages such as high energy density, high operating voltage, and low environmental pollution, and have been widely used in various small portable devices such as mobile phones, digital cameras, laptops, and drones. The demand for higher performance in terms of cycle life and kinetics of lithium-ion batteries is increasing.

[0003] During the charging and discharging process of a secondary battery, the surface of the negative electrode active material inevitably reacts with the electrolyte to form a solid electrolyte interphase (SEI) film. This process consumes the electrolyte, affecting lithium-ion transport in the later stages of the cycle, thus leading to a decrease in the cycle capacity and impacting the battery's cycle performance. To mitigate this issue, increasing the amount of binder allows it to coat the surface of the negative electrode active material particles, reducing the contact area between the material and the electrolyte. However, current technologies typically require excessive amounts of binder to achieve this effect. Too much binder forms an excessively thick coating layer on the surface of the negative electrode active material particles, hindering lithium-ion conduction and deteriorating the battery's kinetic performance. Summary of the Invention

[0004] The purpose of this application is to provide a binder for the negative electrode sheet, a secondary battery, and an electronic device to improve the cycle performance and kinetic performance of the secondary battery. The specific technical solution is as follows:

[0005] A first aspect of this application provides a binder for a negative electrode sheet, wherein the binder comprises a copolymer, and the monomers forming the copolymer include a first monomer, a second monomer, a crosslinking monomer, and a functional monomer, wherein the first monomer comprises at least one selected from acrylic acid or methacrylic acid, and the second monomer is selected from C7 to C6. 19 The acrylate compound, with functional monomers including at least one of allyltriethoxysilane, N-propyltriethoxysilane, or 3-aminopropyltriethoxysilane; the phase angle enhancement rate of the binder is α%, 25≤α≤75; under the conditions of an ambient temperature of 25±5℃, a shear stress of 0.1Pa, and an applied shear stress frequency of 1Hz, the phase angle of the binder is θ0°, the phase angle of the mixture of the binder and the negative electrode active material is θ1°, and the mass ratio of the binder to the negative electrode active material in the mixture is 7:3. In the binder of this application, the first monomer, the second monomer, the crosslinking monomer, and the functional monomer respectively constitute the first monomer unit, the second monomer unit, the crosslinking monomer unit, and the functional monomer unit of the copolymer. The first monomer unit constructs the main structure of the copolymer, which gives the binder good hydrophilicity, which is beneficial for the uniform dispersion of the binder in the negative electrode slurry and its uniform distribution in the negative electrode material layer. The second monomer unit provides hydrophobicity to the copolymer, which is beneficial for improving the affinity between the binder and the negative electrode active material. The crosslinking monomer unit provides a crosslinking structure, which is beneficial for improving ion throughput. The functional monomer unit can further provide affinity between the binder and the negative electrode active material, so that the binder is uniformly attached to the particle surface of the negative electrode active material. The phase angle enhancement rate α% of the binder is within the above range, indicating that the binder of this application can uniformly attach to the particle surface of the negative electrode active material. The binder of this application has a high surface modification ability for the negative electrode active material particles, and its copolymer chain segment porosity is high, which is beneficial for improving the lithium ion throughput. Using the binder of this application on the negative electrode sheet can reduce the contact area between the surface of the negative electrode active material particles and the electrolyte, reduce the side reactions of the electrolyte, and also facilitate the conduction of lithium ions, thereby improving the cycle performance and kinetic performance of the secondary battery.

[0006] In some embodiments of this application, 40 ≤ α ≤ 60. Adjusting the value of α within the above range indicates that the binder can adhere more uniformly to the surface of the negative electrode active material particles, thereby making the use of the binder of this application on the negative electrode sheet more beneficial to improving the cycle performance and kinetic performance of the secondary battery.

[0007] In some embodiments of this application, 12 ≤ θ0 ≤ 18. The value of θ0 within the above range indicates that the binder of this application has a high phase angle, which is beneficial to reducing the contact area between the surface of the negative electrode active material particles and the electrolyte, reducing side reactions of the electrolyte, and also beneficial to the conduction of lithium ions, thereby improving the cycle performance and kinetic performance of the secondary battery.

[0008] In some embodiments of this application, the crosslinking monomer includes at least one of pentaerythritol allyl ether, trimethylolpropane triacrylate, divinylbenzene, ethoxylated trimethylolpropane triacrylate, or pentaerythritol triallyyl ether. Using the above-mentioned crosslinking monomers can adjust the film uniformity of the binder on the surface of the negative electrode active material particles, adjust the microstructure inside the binder film, and increase the porosity between copolymer segments, thereby improving the lithium-ion permeability. This can reduce side reactions between the negative electrode active material particles and the electrolyte, and also facilitate lithium-ion conduction, further improving the cycle performance and kinetic performance of the secondary battery.

[0009] In some embodiments of this application, the first monomer, the second monomer, the crosslinking monomer, and the functional monomer constitute the first monomer unit, the second monomer unit, the crosslinking monomer unit, and the functional monomer unit of the copolymer, respectively. Based on the mass of the copolymer, the mass percentage of the first monomer unit is 67.6% to 87.6%, the mass percentage of the second monomer unit is 10% to 30%, the mass percentage of the crosslinking monomer unit is 0.2% to 1%, and the mass percentage of the functional monomer unit is 1% to 3%. The first monomer unit constructs the main structure of the copolymer, the second monomer provides hydrophobicity to the copolymer, the crosslinking monomer unit provides the crosslinking structure to the copolymer, and the functional monomer provides affinity for the negative electrode active material. Adjusting the mass percentage of the monomer units within the above range can better synergistically leverage the role of each monomer unit in the copolymer, improve the surface modification ability of the binder on the negative electrode active material particles, and ensure that the binder is uniformly attached to the surface of the negative electrode active material particles. This is more conducive to reducing the contact area between the surface of the negative electrode active material particles and the electrolyte, reducing side reactions of the electrolyte, and further improving lithium-ion conduction, thereby improving the cycle performance and kinetic performance of the secondary battery.

[0010] In some embodiments of this application, based on the mass of the copolymer, the mass percentage of the second monomer unit is 15% to 20%, and the mass percentage of the crosslinked monomer unit is 0.3% to 0.5%; and / or, the mass ratio X of the functional monomer unit and the second monomer unit is 0.06 to 0.2. Satisfying at least one of the above characteristics is more conducive to reducing the contact area between the surface of the negative electrode active material particles and the electrolyte, reducing side reactions in the electrolyte, and further improving lithium-ion conduction, thereby enhancing the cycle performance and kinetic performance of the secondary battery.

[0011] In some embodiments of this application, the second monomer is selected from C 10 To C 12 The second monomer is an acrylate compound. Using the aforementioned compound as the second monomer allows the copolymer to possess suitable hydrophobicity, enhancing the affinity between the binder and the negative electrode active material. This facilitates the effective functioning of the second monomer unit, improves the binder's surface modification ability on the negative electrode active material particles, and ensures the binder adheres uniformly to the surface of the negative electrode active material particles, thereby improving the cycle performance and kinetic performance of the secondary battery.

[0012] In some embodiments of this application, the second monomer includes at least one selected from butyl acrylate, isooctyl acrylate, butyl methacrylate, lauryl methacrylate, hexadecyl acrylate, or lauryl acrylate. Using the above-mentioned compounds as the second monomer is more conducive to leveraging the function of the second monomer unit and further improving the cycle performance and kinetic performance of the secondary battery.

[0013] In some embodiments of this application, the weight-average molecular weight (Mw) of the copolymer is between 50,000 g / mol and 100,000 g / mol. Regulating the weight-average molecular weight of the copolymer within this range is more conducive to the adsorption of the binder onto the surface of the negative electrode active material particles, reducing the contact area between the negative electrode active material particle surface and the electrolyte, reducing side reactions in the electrolyte, and also facilitating lithium-ion conduction, thereby improving the cycle performance and kinetic performance of the secondary battery.

[0014] In some embodiments of this application, the swelling degree of the binder in the electrolyte is 10% to 30%, and / or the dissolution rate of the binder in the electrolyte is 2% to 3%. Satisfying at least one of the above characteristics is more conducive to improving the cycle performance and kinetic performance of the secondary battery.

[0015] A second aspect of this application provides a secondary battery comprising a positive electrode and a negative electrode. The negative electrode includes a negative current collector and a negative electrode material layer disposed on at least one surface of the negative current collector. The negative electrode material layer includes the binder provided in any of the foregoing embodiments. The inclusion of the binder in the negative electrode material layer reduces the contact area between the surface of the negative electrode active material particles and the electrolyte, reduces side reactions in the electrolyte, and also facilitates lithium-ion conduction, thereby improving the cycle performance and kinetic performance of the secondary battery.

[0016] In some embodiments of this application, the negative electrode material layer includes a negative electrode active material, which includes graphite and silicon-containing materials. Based on the mass of the negative electrode material layer, the mass percentage of silicon is 1.5% to 30%. By selecting the above-mentioned negative electrode active material and controlling the mass percentage of silicon within the above range, the negative electrode material layer can have a high specific capacity. Combined with the binder of this application, it is more conducive to the capacity utilization of the negative electrode active material, thereby enabling the secondary battery to have a high energy density while also having good cycle performance and kinetic performance.

[0017] In some embodiments of this application, the mass percentage of the binder is 1% to 10% based on the mass of the negative electrode material layer. Regulating the mass percentage of the binder within this range is beneficial for maximizing the binder's function, reducing the contact area between the surface of the negative electrode active material particles and the electrolyte, minimizing side reactions in the electrolyte, and also facilitating lithium-ion conduction, thereby improving the cycle performance and kinetic performance of the secondary battery.

[0018] In some embodiments of this application, the mass percentage of the binder is 2% to 5% based on the mass of the negative electrode material layer. Controlling the mass percentage of the binder within this range is beneficial for better utilizing the binder's function, thereby further improving the cycle performance and kinetic performance of the secondary battery.

[0019] A third aspect of this application provides an electronic device comprising the secondary battery provided in any of the foregoing embodiments. Thus, the electronic device of this application has a long service life and good performance.

[0020] The beneficial effects of this application are:

[0021] This application provides a binder for a negative electrode sheet, a secondary battery, and an electronic device. The binder includes a copolymer, and the monomers forming the copolymer include a first monomer, a second monomer, a crosslinking monomer, and a functional monomer. The first monomer includes at least one of acrylic acid or methacrylic acid, and the second monomer is selected from C7 to C6. 19 The acrylate compound contains functional monomers including at least one of allyltriethoxysilane, N-propyltriethoxysilane, or 3-aminopropyltriethoxysilane; the phase angle enhancement rate of the binder is α%, 25 ≤ α ≤ 75. In the binder of this application, the structural units of the first monomer construct the main structure of the binder, which can make the binder have good hydrophilicity, which is beneficial to the uniform dispersion of the binder in the negative electrode slurry; the second monomer provides hydrophobicity to the copolymer, which is beneficial to improving the affinity between the binder and the negative electrode active material; the crosslinking monomer can provide a crosslinking structure, which is beneficial to improving the ion throughput; the functional monomer can further provide affinity between the binder and the negative electrode active material, so that the binder is uniformly attached to the particle surface of the negative electrode active material. The phase angle enhancement rate α% of the binder is within the above range, indicating that the binder of this application can be uniformly attached to the particle surface of the negative electrode active material. The binder of this application has a high surface modification ability for the negative electrode active material particles, and its copolymer segment porosity is high, which is beneficial to improving the lithium ion throughput. Using the binder of this application on the negative electrode sheet can reduce the contact area between the surface of the negative electrode active material particles and the electrolyte, reduce the side reactions of the electrolyte, and also facilitate the conduction of lithium ions, thereby improving the cycle performance and kinetic performance of the secondary battery.

[0022] Of course, implementing any product or method of this application does not necessarily require achieving all of the advantages described above at the same time. Attached Figure Description

[0023] To more clearly illustrate the technical solutions in the embodiments of this application, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of this application. For those skilled in the art, other embodiments can be obtained based on these accompanying drawings.

[0024] Figure 1 The graph shows the phase angle of the binder in Example 1-1 and the phase angle of the mixture of binder and negative electrode active material as a function of shear stress.

[0025] Figure 2 The graph shows the phase angle of the binder in Comparative Example 5 and the phase angle of the mixture of binder and negative electrode active material as a function of shear stress. Detailed Implementation

[0026] The technical solutions of this application will be clearly and completely described below with reference to the embodiments and accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. All other embodiments obtained by those skilled in the art based on this application are within the scope of protection of this application.

[0027] It should be noted that, in the specific embodiments of this application, a lithium-ion battery is used as an example of a secondary battery to explain this application; however, the secondary battery in this application is not limited to lithium-ion batteries. The specific technical solution is as follows:

[0028] A first aspect of this application provides a binder for a negative electrode sheet, wherein the binder comprises a copolymer, and the monomers forming the copolymer include a first monomer, a second monomer, a crosslinking monomer, and a functional monomer, wherein the first monomer comprises at least one selected from acrylic acid or methacrylic acid, and the second monomer is selected from C7 to C6. 19 The acrylate compound, with functional monomers including at least one of allyltriethoxysilane, N-propyltriethoxysilane, or 3-aminopropyltriethoxysilane; the phase angle enhancement rate of the binder is α%, 25≤α≤75, preferably 40≤α≤60. For example, the value of α can be 25, 28, 30, 35, 40, 44, 45, 50, 53, 55, 59, 60, 65, 70, 75, or a range of any two values ​​therein. Under the conditions of an ambient temperature of 25±5℃, a shear stress of 0.1Pa, and a shear stress application frequency of 1Hz, the phase angle of the binder is θ0°, the phase angle of the mixture of binder and negative electrode active material is θ1°, and the mass ratio of binder to negative electrode active material in the mixture is 7:3.

[0029] In the binder of this application, the first monomer, the second monomer, the crosslinking monomer, and the functional monomer constitute the first monomer unit, the second monomer unit, the crosslinking monomer unit, and the functional monomer unit of the copolymer, respectively. The first monomer unit forms the main structure of the copolymer, giving the binder good hydrophilicity, which is beneficial for uniform dispersion of the binder in the negative electrode slurry and allows it to be evenly distributed in the negative electrode material layer, thus better exerting the binder's function. The second monomer unit provides hydrophobicity to the copolymer, enabling suitable affinity between the binder and the negative electrode active material, which is beneficial for the extension of copolymer chain segments and reduces the possibility of copolymer chain segment curling. This allows the binder to adhere uniformly to the surface of the negative electrode active material particles. Preferably, this enhances the binder's ability to modify the graphite surface, thereby reducing the contact area between the surface of the negative electrode active material particles and the electrolyte, and reducing side reactions of the electrolyte. The crosslinking monomer unit provides the crosslinking structure for the copolymer, which can regulate the film formation of the binder on the surface of the negative electrode active material particles and the microstructure inside the binder film. The copolymer has suitable chain segment mobility, enabling the binder to have a high surface modification ability for the negative electrode active material particles, reducing the contact area between the surface of the negative electrode active material particles and the electrolyte, reducing side reactions of the electrolyte, and the high porosity between copolymer chain segments is beneficial to improving lithium ion permeability. The functional monomer can further provide the binder with affinity for the negative electrode active material, allowing the binder to adhere more uniformly to the surface of the negative electrode active material particles. Preferably, it is beneficial to improve the surface modification ability of the binder on silicon-containing materials, thereby helping to reduce the contact area between the surface of the negative electrode active material particles and the electrolyte, and reducing side reactions of the electrolyte. In addition, there is an interaction force between the above-mentioned functional monomer and the second monomer. Through the hydrophobic compatibility between alkyl groups, the functional monomer can be linked to the chain segments of the copolymer through the above-mentioned interaction, which can further improve the utilization rate of the functional monomer and thus better exert the role of the functional monomer. Therefore, by selecting the monomers of the aforementioned copolymer, the binder can not only be uniformly distributed in the negative electrode material layer, but also improve the surface modification ability of the binder on the negative electrode active material particles, allowing the binder to adhere uniformly to the surface of the negative electrode active material particles. Furthermore, the high porosity between the copolymer chain segments is beneficial for improving the lithium-ion permeability. Thus, using the binder of this application in the negative electrode sheet can reduce the contact area between the surface of the negative electrode active material particles and the electrolyte, reduce side reactions in the electrolyte, and also facilitate lithium-ion conduction, thereby improving the cycle performance and kinetic performance of the secondary battery.

[0030] Furthermore, the inventors discovered that, due to the strong inter-segmental forces and entanglement of copolymer segments, the copolymer exhibits a relatively rigid characteristic. Under stress, elasticity dominates, resulting in a low phase angle. When the binder is mixed with the negative electrode active material, more binder is adsorbed onto the surface of the negative electrode active material particles, reducing free binder, decreasing copolymer segment entanglement, and reducing inter-segmental forces. Consequently, under stress, rigidity decreases, and the proportion of elasticity weakens, leading to an increased phase angle. Therefore, the phase angle enhancement rate is used to characterize the binder's surface modification ability on the particles. A higher phase angle enhancement rate indicates a higher surface modification ability of the binder on the negative electrode active material particles, a more uniform distribution on the particle surface, and a greater amount of binder adhering to the particle surface. When the value of α is too small, for example, less than 25, the phase angle enhancement rate is too small, indicating that the binder has a low surface modification ability for the negative electrode active material particles and cannot uniformly adhere to the surface of the negative electrode active material particles, which is not conducive to the role of the binder. When the value of α is too large, for example, greater than 75, the phase angle enhancement rate is too large, and too much binder adheres to the surface of the negative electrode active material, causing ion conduction in the negative electrode material layer to be hindered and deteriorating the kinetic performance of the lithium-ion battery. The phase angle enhancement rate α% of the binder is within the above range, indicating that the binder of this application can uniformly adhere to the surface of the negative electrode active material particles and the binder has a high surface modification ability for the negative electrode active material particles. Therefore, using the binder of this application for the negative electrode sheet can reduce the contact area between the surface of the negative electrode active material particles and the electrolyte, reduce the side reactions of the electrolyte, and help improve the cycle performance and kinetic performance of the secondary battery.

[0031] In some embodiments of this application, 12 ≤ θ0 ≤ 18, for example, θ0 can be 12, 13, 14, 15, 16, 17, 18, or any two of these values. Commonly used binders, such as polyacrylic acid binders, have a phase angle of 4° to 6°. The value of θ0 for the binder in this application falls within the above range, indicating that the binder has a higher phase angle. A binder with a higher phase angle has a greater surface modification capability for the negative electrode active material particles, thereby further reducing the contact area between the surface of the negative electrode active material particles and the electrolyte, reducing side reactions in the electrolyte, and also facilitating lithium-ion conduction, improving the cycle performance and kinetic performance of the secondary battery.

[0032] In some embodiments of this application, the crosslinking monomer includes at least one of pentaerythritol allyl ether, trimethylolpropane triacrylate, divinylbenzene, ethoxylated trimethylolpropane triacrylate, or pentaerythritol triallyyl ether. Using the above-mentioned crosslinking monomers can adjust the film uniformity of the binder on the surface of the negative electrode active material particles, adjust the microstructure inside the binder film, and increase the porosity between copolymer segments, thereby improving the lithium-ion permeability. This can reduce side reactions between the negative electrode active material particles and the electrolyte, and also facilitate lithium-ion conduction, further improving the cycle performance and kinetic performance of the secondary battery.

[0033] In some embodiments of this application, the first monomer, the second monomer, the crosslinking monomer, and the functional monomer constitute the first monomer unit, the second monomer unit, the crosslinking monomer unit, and the functional monomer unit of the copolymer, respectively. Based on the mass of the copolymer, the mass percentage A of the first monomer unit is 67.6% to 87.6%, the mass percentage B of the second monomer unit is 10% to 30%, the mass percentage C of the crosslinking monomer unit is 0.2% to 1%, and the mass percentage D of the functional monomer unit is 1% to 3%. For example, the mass percentage A of the first monomer unit can be 67.6%, 70%, 71%, 73%, 75%, 77%, 80%, 83%, 85%, 86%, 87%, 87.6%, or a range consisting of any two of these values, and the mass percentage B of the second monomer unit can be 10%, 13%, 15%, 18%, 20%, 22%, 24%, 25%, 28%, 30%, or a range consisting of any two of these values. The mass percentage C of the crosslinking monomer unit can be 0.2%, 0.3%, 0.35%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, or any combination of two values ​​within this range. The mass percentage D of the functional monomer unit can be 1%, 1.1%, 1.5%, 1.6%, 1.8%, 2%, 2.4%, 2.8%, 3%, or any combination of two values ​​within this range. Controlling the mass percentage of the first monomer unit within the above range allows the binder to have a suitable molecular weight and water solubility, which is beneficial for the uniform dispersion of the binder in the negative electrode slurry, thereby better utilizing the binder's function. By controlling the mass percentage of the second monomer unit within the aforementioned range, the binder can possess suitable hydrophobicity and affinity with the negative electrode active material, which is beneficial for the expansion of copolymer segments and reduces the possibility of their curling. This allows the binder to adhere uniformly to the surface of the negative electrode active material particles, thereby reducing the contact area between the surface of the negative electrode active material particles and the electrolyte, and minimizing electrolyte side reactions. Controlling the mass percentage of the crosslinking monomer unit within the aforementioned range allows the copolymer to have a suitable degree of crosslinking and porosity. This gives the copolymer suitable chain segment mobility, enabling the binder to have a high surface modification ability on the negative electrode active material particles, further reducing the contact area between the surface of the negative electrode active material particles and the electrolyte, minimizing electrolyte side reactions, and resulting in higher inter-segment porosity, which is beneficial for improving lithium ion permeability. Controlling the mass percentage of the functional monomer unit within the aforementioned range further enhances the role of the functional monomer, allowing the binder to adhere more uniformly to the surface of the negative electrode active material particles, further reducing the contact area between the surface of the negative electrode active material particles and the electrolyte, and minimizing electrolyte side reactions.Therefore, adjusting the mass percentage of the aforementioned individual units within the above range is more conducive to leveraging the role of the binder and further improving the cycle performance and kinetic performance of the secondary battery.

[0034] In some embodiments of this application, the mass percentage of the second monomer unit is 15% to 20% and the mass percentage of the crosslinking monomer unit is 0.3% to 0.5%, based on the mass of the copolymer. Controlling the mass percentages of the second monomer unit and the crosslinking monomer unit within these ranges allows for better utilization of their functions, reduces the contact area between the negative electrode active material particles and the electrolyte, minimizes side reactions in the electrolyte, and further improves lithium-ion conduction, thereby enhancing the cycle performance and kinetic performance of the secondary battery.

[0035] In some embodiments of this application, the mass ratio X of the functional monomer unit and the second monomer unit is from 0.06 to 0.2. For example, the value of X can be 0.06, 0.07, 0.08, 0.09, 0.1, 0.14, 0.15, 0.18, 0.2, or a range of any two values ​​therein. Adjusting the mass ratio of the functional monomer unit and the second monomer unit within the above range can further improve the utilization rate of the functional monomer, thereby better leveraging its role, enhancing the surface modification ability of the binder on the negative electrode active material, and more effectively reducing the contact area between the negative electrode active material particle surface and the electrolyte, thus reducing side reactions in the electrolyte. Simultaneously, it further improves lithium-ion conduction and enhances the cycle performance and kinetic performance of the secondary battery.

[0036] In some embodiments of this application, the second monomer is selected from C 10 To C 12 Acrylate compounds. For example, the second monomer can be C 10 Acrylic ester compounds, C 11 Acrylic ester compounds, C 12 The copolymer contains an acrylate compound, preferably an isooctyl acrylate. Using the aforementioned compound as the second monomer allows the copolymer to possess suitable hydrophobicity and facilitates chain segment extension. This enhances the affinity between the binder and the negative electrode active material, facilitating the effective function of the second monomer unit and improving the binder's surface modification capability on the negative electrode active material particles. This results in the binder uniformly adhering to the surface of the negative electrode active material particles, thereby improving the cycle performance and kinetic performance of the secondary battery.

[0037] In some embodiments of this application, the second monomer includes at least one selected from butyl acrylate, isooctyl acrylate, butyl methacrylate, lauryl methacrylate, hexadecyl acrylate, or lauryl acrylate. Using the above-mentioned compounds as the second monomer allows the copolymer to possess suitable hydrophobicity, making the chain segments easier to extend. This enhances the affinity between the binder and the negative electrode active material, better facilitating the function of the second monomer unit, further improving the binder's surface modification ability on the negative electrode active material particles, ensuring uniform adhesion of the binder to the surface of the negative electrode active material particles, and further improving the cycle performance and kinetic performance of the secondary battery.

[0038] In this application, the number of carbon atoms in an acrylate compound refers to the sum of the number of carbon atoms in the main chain and branches of the acrylate compound, such as butyl acrylate having a carbon number of C7, isooctyl acrylate having a carbon number of C11, butyl methacrylate having a carbon number of C8, lauryl methacrylate having a carbon number of C16, hexadecyl acrylate having a carbon number of C19, and lauryl acrylate having a carbon number of C15.

[0039] In some embodiments of this application, the weight-average molecular weight (Mw) of the copolymer is from 50,000 g / mol to 100,000 g / mol. For example, the weight-average molecular weight (Mw) of the copolymer can be 50,000 g / mol, 60,000 g / mol, 70,000 g / mol, 80,000 g / mol, 90,000 g / mol, 100,000 g / mol, or a range consisting of any two of these values. Controlling the weight-average molecular weight of the copolymer within the above range allows the copolymer to have hydrophilicity or hydrophobicity that is closer to that of the negative electrode active material, resulting in higher affinity between the copolymer and the negative electrode active material. This facilitates adsorption onto the surface of the negative electrode active material, allowing the binder to uniformly modify the surface of the negative electrode active material, achieving a surface modification effect. This reduces the contact area between the surface of the negative electrode active material particles and the electrolyte, reduces side reactions in the electrolyte, and also promotes lithium-ion conduction, improving the cycle performance and kinetic performance of the secondary battery.

[0040] In some embodiments of this application, the swelling degree of the binder in the electrolyte is 10% to 30%, for example, the swelling degree of the binder in the electrolyte can be 10%, 14%, 15%, 18%, 20%, 24%, 25%, 28%, 30%, or a range of any two of these values. The fact that the swelling degree of the binder in the electrolyte is within the above range indicates that the binder of this application has a low swelling degree and does not easily swell after immersion in the electrolyte, indicating low affinity with the electrolyte. This reduces the probability of contact between the electrolyte and the particles of the negative electrode active material, reduces side reactions in the electrolyte, and thus improves the cycle performance and kinetic performance of the secondary battery.

[0041] In some embodiments of this application, the dissolution rate of the binder in the electrolyte is 2% to 3%, for example, the dissolution rate of the binder in the electrolyte can be 2%, 2.1%, 2.2%, 2.4%, 2.5%, 2.7%, 2.9%, 3%, or a range of any two of these values. A dissolution rate of the binder in the electrolyte within the above range indicates that the binder has good stability in the electrolyte. A low dissolution rate allows it to better fulfill its role in the use of secondary batteries, reduces the exposed area of ​​active sites on the surface of the negative electrode active material particles, reduces side reactions in the electrolyte, and is more conducive to improving the cycle performance and kinetic performance of the secondary battery.

[0042] This application does not impose any particular limitation on the preparation method of the adhesive, as long as it can achieve the purpose of this application, for example, it may include but is not limited to the following steps:

[0043] (1) First, mix water, pH adjuster and initiator evenly to obtain mixture E.

[0044] (2) Mix the first monomer and the second monomer evenly to obtain monomer mixture one. Take 30% to 60% of the above monomer mixture one by mass and add it to mixture E. Stir evenly at room temperature and then carry out the first reaction. The temperature T1 of the first reaction is 70℃ to 90℃ and the reaction time t2 is 3 hours (h) to 5 hours to obtain mixture H.

[0045] (3) Add the crosslinking monomer and functional monomer to the remaining monomer mixture one, and stir until homogeneous to obtain monomer mixture two. Add monomer mixture two to the above mixture H dropwise, with a dropwise addition time t. a The dripping time is 2 to 4 hours, during which the temperature of the above mixture H is maintained at T. a The temperature is 70℃ to 90℃. After the addition is complete, a second reaction is carried out at a temperature T2 of 70℃ to 90℃ for a time t2 of 0.5h to 2h. After the reaction is complete, a mixture K containing the binder is obtained.

[0046] (4) Add pH adjuster to neutral pH in mixture K, and finally filter and vacuum process to remove residual monomers and separate to obtain binder.

[0047] This application does not impose any particular limitation on the pH adjuster, as long as it achieves the purpose of this application. For example, it may include, but is not limited to, at least one of lithium carbonate, lithium hydroxide, or sodium hydroxide. This application also does not impose any particular limitation on the initiator, as long as it achieves the purpose of this application. For example, the initiator may include, but is not limited to, at least one of the following: inorganic peroxides, such as sodium persulfate, potassium persulfate, ammonium persulfate, a composite initiator of ammonium persulfate and sodium bisulfite, potassium superphosphate, and hydrogen peroxide; organic peroxides, such as tert-butyl peroxide, cumene hydroperoxide, terpene hydrogen peroxide, di-tert-butyl peroxide, tert-butylcumyl peroxide, acetyl peroxide, isobutyl peroxide, octanoyl peroxide, benzoyl peroxide, 3,5,5-trimethylhexanol peroxide, and tert-butyl peroxide; and azo compounds, such as at least one of azobisisobutyronitrile, azobis-2,4-dimethylpentanonitrile, azobiscyclohexaneformitrile, or dimethyl azobisisobutyronitrile.

[0048] In this application, based on the total mass of the monomers, the mass percentage of the first monomer is 71% to 87%, the mass percentage of the second monomer is 10% to 30%, the mass percentage of the crosslinking monomer is 0.2% to 1%, and the mass percentage of the functional monomer is 1% to 3%. The aforementioned "total mass of monomers" refers to the sum of the masses of the first monomer, second monomer, crosslinking monomer, and functional monomer. The mass ratio of the total mass of monomers to water is 1:(3 to 19), the mass ratio of the total mass of monomers to the initiator is 1:(0.025 to 0.1), and the mass ratio of the total mass of monomers to the pH adjuster is 1:(0.025 to 0.1). This application does not impose any particular limitation on the above stirring, as long as the purpose of this application is achieved. For example, the stirring speed can be 200 rpm to 300 rpm, and the stirring method can be magnetic stirring or single-bar stirring. This application does not impose any particular limitation on the dropping rate, as long as the purpose of this application is achieved, for example, the dropping rate can be 0.1 mL / s to 1 mL / s.

[0049] This application does not impose any particular restrictions on the vacuum treatment process for removing residual monomers, as long as it achieves the purpose of this application. For example, it can be achieved by using a vacuum condition of -60 kPa to -80 kPa at room temperature and a stirring speed of 200 rpm to 300 rpm for 1.5 h to 3 h.

[0050] In step (4) above, after vacuum treatment to remove residual monomers, the resulting binder is dispersed in the solvent remaining from the reaction and exists in an emulsion state. It can be adjusted to a suitable solid content and directly used in the preparation of the negative electrode slurry. Alternatively, those skilled in the art can dry it according to actual needs to obtain solid particles of the binder, and then add water as a solvent in the preparation of the negative electrode sheet to obtain the binder slurry. This application does not impose any particular limitations on this, as long as the purpose of this application can be achieved. The drying temperature can be from 80°C to 120°C, and the drying time can be from 2 hours to 10 hours.

[0051] This application also provides a binder composition comprising the binder, pH adjuster, and water provided in the first aspect of this application. Based on the mass of the binder composition, the binder comprises 10% to 20% by mass, the pH adjuster comprises 0.5% to 1% by mass, and the balance is water. Using a binder composition with the above characteristics to prepare a negative electrode sheet allows for more uniform dispersion of the binder in the negative electrode material layer. It also improves the surface modification ability of the binder on the negative electrode active material, reduces the contact area between the negative electrode active material particles and the electrolyte, reduces side reactions in the electrolyte, and further improves lithium-ion conduction, thereby enhancing the cycle performance and kinetic performance of the secondary battery.

[0052] A second aspect of this application provides a secondary battery comprising a positive electrode and a negative electrode. The negative electrode includes a negative current collector and a negative electrode material layer disposed on at least one surface of the negative current collector. The negative electrode material layer includes a binder provided in any of the foregoing embodiments. The binder of this application has a high surface modification capability for the negative electrode active material particles, and its copolymer segment porosity is high, which is beneficial to improving the lithium-ion permeability. The negative electrode material layer including the binder of this application can reduce the contact area between the surface of the negative electrode active material particles and the electrolyte, reduce side reactions of the electrolyte, and also facilitate lithium-ion conduction, thereby improving the cycle performance and kinetic performance of the secondary battery.

[0053] In some embodiments of this application, the negative electrode material layer includes a negative electrode active material, which includes graphite and silicon-containing materials. Based on the mass of the negative electrode material layer, the mass percentage of silicon element is 1.5% to 30%, for example, the mass percentage of silicon element can be 1.5%, 3%, 5%, 10%, 15%, 20%, 23%, 25%, 30%, or a range of any two values ​​therein. By selecting the above-mentioned negative electrode active material and controlling the mass percentage of silicon element within the above range, the negative electrode material layer can have a high specific capacity. Combined with the binder of this application, it is more conducive to the capacity utilization of the negative electrode active material, thereby enabling the secondary battery to have a high energy density while having good cycle performance and kinetic performance.

[0054] In this application, the silicon-containing material includes at least one of silicon, silicon-carbon, or silicon-oxygen, and the graphite may include natural graphite and artificial graphite. This application does not have any particular limitations in this regard, as long as the purpose of this application can be achieved. Optionally, the negative electrode active material may also include carbon materials such as hard carbon.

[0055] In some embodiments of this application, the mass percentage of the binder is 1% to 10%, preferably 2% to 5%, based on the mass of the negative electrode material layer. For example, the mass percentage of the binder can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or a range consisting of any two of these values. Controlling the mass percentage of the binder within the above range is beneficial for maximizing the binder's effect, reducing the contact area between the surface of the negative electrode active material particles and the electrolyte, reducing side reactions in the electrolyte, and also facilitating lithium-ion conduction, thereby improving the cycle performance and kinetic performance of the secondary battery.

[0056] The phrase "the negative electrode material layer is disposed on at least one surface of the negative electrode current collector" means that the negative electrode material layer can be disposed on one surface of the negative electrode current collector along its own thickness direction, or on two surfaces of the negative electrode current collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of ​​the negative electrode current collector surface, or it can be a part of the negative electrode current collector surface. This application has no particular limitation, as long as the purpose of this application can be achieved.

[0057] This application does not impose any particular limitation on the negative electrode current collector, as long as it achieves the purpose of this application. For example, it may include copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, or a composite current collector. For example, the composite current collector may be a lithium-copper composite current collector, a carbon-copper composite current collector, a nickel-copper composite current collector, a titanium-copper composite current collector, etc. This application does not impose any particular limitation on the thickness of the negative electrode material layer, as long as it achieves the purpose of this application. For example, the thickness of the negative electrode material layer may be 30 μm to 120 μm. This application does not impose any particular limitation on the thickness of the negative electrode current collector, as long as it achieves the purpose of this application. For example, the thickness of the negative electrode current collector may be 4 μm to 15 μm.

[0058] In some embodiments, the negative electrode material layer may further include a conductive agent and a dispersant. This application does not impose any particular limitation on the types of conductive agents and dispersants, as long as they achieve the purpose of this application. For example, the conductive agent may include, but is not limited to, at least one of conductive carbon black (Super P), carbon nanotubes (CNTs), carbon fibers, flake graphite, graphene, metallic materials, or conductive polymers. The conductive carbon black may include, but is not limited to, at least one of acetylene black or Ketjen black. The aforementioned carbon nanotubes may include, but are not limited to, single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The aforementioned carbon fibers may include, but are not limited to, vapor-grown carbon fibers (VGCF) and / or carbon nanofibers. The aforementioned metallic materials may include, but are not limited to, metal powders and / or metal fibers; specifically, the metal may include, but is not limited to, at least one of copper, nickel, aluminum, or silver. The aforementioned conductive polymers may include, but are not limited to, at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene, or polypyrrole. For example, the dispersant may include, but is not limited to, at least one of sodium carboxymethyl cellulose or lithium carboxymethyl cellulose. This application does not impose any particular limitation on the mass percentage content of the conductive agent and dispersant in the negative electrode material layer; those skilled in the art can select them according to actual needs, as long as the purpose of this application is achieved. For example, the mass percentage of conductive agent can be 0% to 5%, and the mass percentage of dispersant can be 0.2% to 2%.

[0059] In this application, the positive electrode includes a positive current collector and a positive electrode material layer disposed on at least one surface of the positive current collector. The phrase "positive electrode material layer disposed on at least one surface of the positive current collector" means that the positive electrode material layer can be disposed on one surface of the positive current collector along its thickness direction, or on two surfaces of the positive current collector along its thickness direction. It should be noted that "surface" here can refer to the entire surface area of ​​the positive current collector, or only a portion thereof; this application does not impose any particular limitation, as long as the purpose of this application is achieved.

[0060] This application does not impose any particular limitation on the positive electrode current collector, as long as it achieves the purpose of this application. For example, it may include aluminum foil, aluminum alloy foil, or composite current collectors (such as aluminum-carbon composite current collectors). This application also does not impose any particular limitation on the thickness of the positive electrode current collector and the positive electrode material layer, as long as it achieves the purpose of this application. For example, the thickness of the positive electrode current collector may be 5 μm to 20 μm, and the thickness of the positive electrode material layer may be 30 μm to 120 μm.

[0061] The positive electrode material layer includes a positive electrode active material. This application does not impose any particular limitation on the positive electrode active material, as long as it can achieve the purpose of this application. For example, the positive electrode active material may include, but is not limited to, lithium nickel cobalt manganese oxide (e.g., NCM811, NCM622, NCM523, NCM111), lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide (LiCoO2), lithium manganese oxide, lithium manganese iron phosphate, or lithium titanate.

[0062] The positive electrode material layer may further include a positive electrode conductive agent and a positive electrode binder. This application does not impose any particular limitation on the positive electrode conductive agent, as long as it can achieve the purpose of this application. For example, the positive electrode conductive agent may include, but is not limited to, at least one of conductive carbon black (SuperP), carbon nanotubes (CNTs), carbon fibers, flake graphite, graphene, metallic materials, or conductive polymers. The conductive carbon black may include, but is not limited to, at least one of acetylene black or Ketjen black. The aforementioned carbon nanotubes may include, but are not limited to, single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The aforementioned carbon fibers may include, but are not limited to, vapor-grown carbon fibers (VGCF) and / or carbon nanofibers. The aforementioned metallic materials may include, but are not limited to, metal powders and / or metal fibers. Specifically, the metal may include, but is not limited to, at least one of copper, nickel, aluminum, or silver. The aforementioned conductive polymer may include, but is not limited to, at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene, or polypyrrole. This application does not impose any particular restrictions on the positive electrode binder, as long as it can achieve the purpose of this application. For example, the positive electrode binder may include, but is not limited to, at least one of polyacrylic acid, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyimide, polyvinyl alcohol, polyamide-imide, styrene-butadiene rubber or polyvinylidene fluoride.

[0063] This application does not impose any particular restrictions on the mass ratio of positive electrode active material, positive electrode conductive agent, and positive electrode binder in the positive electrode material layer. Those skilled in the art can choose according to actual needs, as long as the purpose of this application can be achieved.

[0064] In this application, the secondary battery also includes a separator. This application does not impose any particular limitation on the separator, as long as it achieves the purpose of this application. For example, the separator material may include, but is not limited to, at least one of polyethylene (PE), polyolefins (PO) primarily composed of polypropylene (PP), polyester (e.g., polyethylene terephthalate (PET) film), cellulose, polyimide (PI), polyamide (PA), spandex, or aramid. The separator type may include at least one of woven membrane, nonwoven membrane, microporous membrane, composite membrane, rolled membrane, or spun membrane. In some embodiments, the separator may include a substrate layer and a surface treatment layer. The substrate layer may be a nonwoven fabric, membrane, or composite membrane with a porous structure, and the material of the substrate layer may include at least one of polyethylene, polypropylene, polyethylene terephthalate, or polyimide. Optionally, a polypropylene porous membrane, a polyethylene porous membrane, a polypropylene nonwoven fabric, a polyethylene nonwoven fabric, or a polypropylene-polyethylene-polypropylene porous composite membrane may be used. In this application, there is no particular limitation on the thickness of the diaphragm, as long as it can achieve the purpose of this application. For example, the thickness of the diaphragm can be from 3 μm to 30 μm.

[0065] In this application, the secondary battery also includes an electrolyte, which comprises lithium salts and non-aqueous solvents. This application does not impose any particular limitation on the lithium salt, as long as it achieves the purpose of this application. For example, the lithium salt may include, but is not limited to, at least one of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, Li2SiF6, lithium bis(oxalato)borate (LiBOB), or lithium difluoroborate. This application does not impose any particular limitation on the content of lithium salts in the electrolyte, as long as it achieves the purpose of this application. This application does not impose any particular limitation on the non-aqueous solvent, as long as it achieves the purpose of this application. For example, the non-aqueous solvent may include, but is not limited to, at least one of carbonate compounds, carboxylic acid ester compounds, ether compounds, or other organic solvents. The aforementioned carbonate compounds may include, but are not limited to, at least one of chain carbonate compounds, cyclic carbonate compounds, or fluorocarbonate compounds. The aforementioned chain carbonate compounds may include, but are not limited to, at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), or methyl ethyl carbonate (MEC). The aforementioned cyclic carbonates may include, but are not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), butyl carbonate (BC), or vinyl ethylene carbonate (VEC). Fluorinated carbonate compounds may include, but are not limited to, at least one of fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, or trifluoromethylethylene carbonate. The aforementioned carboxylic acid ester compounds may include, but are not limited to, at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanolactone, valproic acid lactone, or caprolactone. The aforementioned ether compounds may include, but are not limited to, at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran, or tetrahydrofuran. The aforementioned other organic solvents may include, but are not limited to, at least one of dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolium ketone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, or trioctyl phosphate. This application does not impose any particular limitation on the content of non-aqueous solvents in the electrolyte, as long as the purpose of this application is achieved.

[0066] The secondary battery also includes a casing for housing the positive electrode, separator, negative electrode, and electrolyte, as well as other components known in the field of secondary batteries. This application does not limit the scope of these other components. This application does not impose any particular limitation on the casing; it can be a casing known in the art, as long as it achieves the purpose of this application. For example, the casing can be a rigid casing or a flexible casing. The material of the rigid casing can be metal; this application does not limit the type of metal and can use known metal rigid casings, as long as they achieve the purpose of this application. The flexible casing can be a metal plastic film, such as aluminum-plastic film, steel-plastic film, etc.

[0067] The fabrication process of the secondary battery described in this application is well known to those skilled in the art, and this application does not impose any particular limitations. For example, the fabrication process of the secondary battery may include, but is not limited to, the following steps: stacking the positive electrode, separator, and negative electrode in sequence, and performing operations such as winding and folding as needed to obtain a wound electrode assembly; placing the electrode assembly into a housing; injecting electrolyte into the housing and sealing it to obtain the secondary battery. Alternatively, stacking the positive electrode, separator, and negative electrode in sequence, and then fixing the four corners of the entire stacked structure with tape to obtain a stacked electrode assembly; placing the electrode assembly into a housing; injecting electrolyte into the housing and sealing it to obtain the secondary battery. In addition, overcurrent protection elements, conductive plates, etc., may be placed in the housing as needed to prevent pressure rise and overcharging / discharging inside the secondary battery.

[0068] A third aspect of this application provides an electronic device comprising the secondary battery provided in any of the foregoing embodiments. Thus, the electronic device of this application has a long service life and good performance.

[0069] This application does not specifically limit the type of electronic device; it can be any electronic device known in the prior art. In some embodiments of this application, the electronic device may include, but is not limited to, laptops, pen input computers, mobile computers, e-book players, portable telephones, portable fax machines, portable copiers, portable printers, stereo headphones, video recorders, LCD TVs, portable cleaners, portable CD players, mini CDs, transceivers, electronic notebooks, calculators, memory cards, portable recorders, radios, backup power supplies, motors, automobiles, motorcycles, electric bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries, and lithium-ion capacitors, etc.

[0070] Example

[0071] The embodiments and comparative examples provided below illustrate the implementation of this application in more detail. Various tests and evaluations were conducted according to the methods described below. Furthermore, unless otherwise specified, "parts" and "%" are quality standards.

[0072] Test methods and equipment:

[0073] Phase angle test:

[0074] The phase angle was measured using a rotational rheometer (TA Instruments, USA, model: DHR-2), and the phase angle enhancement rate α% of the binder was calculated. The binder was dispersed in deionized water to obtain an aqueous dispersion with a solid content of 15%. This aqueous dispersion was loaded onto the base plate of the testing instrument, excess sample was scraped off, and the test parameters were set as follows: temperature: 25±5℃, frequency: 1Hz, shear stress range: 0.01Pa to 8Pa. The test was then started with amplitude scanning to obtain the phase angle curve of the binder. Finally, the phase angle θ0 of the binder was obtained by analyzing the curve. Alternatively, the binder was first dispersed in deionized water, and then a negative electrode active material (with the same composition as in Example 1-1) was added. The mass ratio of binder to negative electrode active material was 7:3, resulting in an aqueous dispersion of a mixture of binder and negative electrode active material with a solid content of 21.4wt%. Then, the mixture was stirred at 1000 rpm for 1 hour to obtain an aqueous dispersion of the binder and the negative electrode active material. The aqueous dispersion of the binder and the negative electrode active material was then loaded onto the base plate of the testing instrument for testing. The testing procedure was the same as the phase angle test procedure of the binder, and the phase angle θ1 of the binder and the negative electrode active material was obtained.

[0075] Compositional testing of copolymers:

[0076] The monomer composition of the copolymer after pyrolysis was determined by pyrolysis gas chromatography-mass spectrometry (py GC-MS), and the mass percentage of monomer units in the copolymer was analyzed. The binder was dried in an 80℃ oven for 8 hours, and then tested using a pyrolysis gas chromatography-mass spectrometry instrument (Agilent 7890B / 5977B), a mass selective detector (MSD), a pyrolysis gas injector (EGA / PY-3030D), a column oven temperature range of 40℃ to 320℃, and a pyrolyzer temperature range of 40℃ to 800℃.

[0077] Weight-average molecular weight test:

[0078] Gel permeation chromatography (GPC) was used to characterize the weight-average molecular weight (Mw) of the binder. The instrument was an Agilent 1260 HPLC system equipped with a refractive index detector (RID), and the column model was 79911GP-502. Specific procedures included: dispersing 5 mg of binder sample in 2 mL of deionized water (HPLC grade), setting the column temperature to 30 °C, using HPLC grade water as the mobile phase, and a flow rate of 1.0 mL / min. -1 .

[0079] Swelling degree and dissolution rate test:

[0080] Take an adhesive sample and weigh its mass (W0). Then, immerse the sample in the electrolyte for 48 hours (h). Wipe the solvent off the sample surface and weigh the swollen sample (W1). Weigh each sample three times during the test. The swelling degree of the adhesive (%) is calculated as (W1-W0) / W0 × 100%. Dry the swollen sample at 80℃ for 8 hours and weigh the dried sample as W2. The dissolution rate of the adhesive (%) is calculated as (W2-W0) / W0 × 100%.

[0081] The electrolyte used above is the same as that in Example 1-1.

[0082] Silicon content by mass percentage test:

[0083] Disassemble the lithium-ion battery and remove the negative electrode. Secure the negative electrode to the sample stage using conductive carbon adhesive, and place the sample stage onto the support. Place the support and sample stage into the cross-section polishing apparatus (CP), and evacuate to 10°C. -4 After Pa, argon gas was used to cut along the thickness direction of the negative electrode sheet. The sample section after CP cutting was placed on the SEM sample stage with the cross-section facing upwards and observed using a Philips XL-30 field emission scanning electron microscope (SEM). The accelerating voltage was 10 kV, the emission current was 10 mA, and the magnification was 3000x. The mass percentage of silicon in the negative electrode material layer was determined using the X-ray energy dispersive spectroscopy (EDS) instrument equipped with the SEM.

[0084] Adhesive mass percentage test:

[0085] Thermogravimetric analysis (TGA) was used to characterize the mass percentage of binder in the negative electrode. The lithium-ion battery was disassembled, the negative electrode was removed, cleaned, and a 5mm × 5mm sample was placed on the sample tray of the TGA instrument, with the initial mass recorded. The TGA temperature program was set at a heating rate of 10℃ / min, with the temperature range increasing from room temperature to the upper limit of 500℃. After the heating was completed, the thermogravimetric curve of the binder was obtained. The mass loss between 300℃ and 450℃ represented the mass loss of the binder, and the mass percentage of the binder was calculated.

[0086] Cyclic performance test:

[0087] The cycle performance of lithium-ion batteries is evaluated by their capacity retention rate. A higher capacity retention rate indicates better cycle performance, and vice versa. The test procedure is as follows: The lithium-ion battery is placed in a constant temperature chamber at 25±2℃ and left to stand for 30 minutes. Then, it is charged at a constant current of 0.5C to the charging cutoff voltage of 4.45V, followed by constant voltage charging to a current of 0.05C. After standing for 10 minutes, it is discharged at 0.5C to the discharge cutoff voltage of 3.0V. This constitutes one charge-discharge cycle. The initial discharge capacity is recorded as C1. This charge-discharge cycle is repeated 500 times, and the discharge capacity on the 500th cycle is recorded as C2. The capacity retention rate (%) of the lithium-ion battery is then calculated as C2 / C1 × 100%.

[0088] Dynamic performance testing:

[0089] The kinetic performance of a secondary battery is evaluated using DC impedance (DCR). A higher DCR value indicates better kinetic performance, and vice versa. The lithium-ion battery is placed in a constant-temperature chamber at 10±2℃ for 2 hours to achieve a constant temperature. It is then charged at a constant current of 0.5C to 4.2V, followed by a constant current of 0.3C to 4.45V, and then charged at a constant voltage of 4.45V until the current reaches 0.02C. The battery is then allowed to rest for 30 minutes. Next, it is discharged at a constant current of 0.1C to 3.4V and allowed to rest for 60 minutes, reaching 50% SOC. The voltage at this point is recorded as V1. Finally, it is discharged at a constant current of I = 1C for 10 seconds, with voltage changes recorded 10 times per second. The voltage at the end of the discharge is recorded as V2. The DC impedance DCR is then calculated as |V1 - V2| / I. This test is repeated three times, and the average value is used to obtain the DCR of the lithium-ion battery, expressed in mΩ.

[0090] The lithium-ion battery used as an example in this application has a charging cut-off voltage of 4.45V and a discharging cut-off voltage of 3.0V. The charging and discharging cut-off voltages of the lithium-ion battery can be based on the printing on the battery's outer packaging at the factory.

[0091] Example 1-1

[0092] <Preparation of Adhesive>

[0093] (1) Add deionized water, pH adjuster lithium carbonate and initiator ammonium persulfate to a three-necked flask and mix well to obtain mixture E.

[0094] (2) Mix the first monomer acrylic acid and the second monomer isooctyl acrylate (2-EHA) evenly to obtain monomer mixture one. Take 40% of the above monomer mixture one by mass and add it to mixture E. Stir evenly at room temperature, and then carry out the first reaction. The temperature T1 of the first reaction is 80℃ and the reaction time t1 is 4h to obtain mixture H.

[0095] (3) The crosslinking monomer pentaerythritol allyl ether (PEAE) and the functional monomer 3-aminopropyltriethoxysilane (APTES) were added to the remaining monomer mixture one and stirred until homogeneous to obtain monomer mixture two. Monomer mixture two was added dropwise to the above mixture H, with a dropwise addition time t. a The process takes 3 hours, during which the temperature of the above mixture H is maintained at T. a The temperature was set at 80℃. After the addition was complete, a second reaction was carried out at a temperature of 80℃ for 1 hour. After the reaction was completed, a mixture K containing the binder was obtained.

[0096] (4) Add lithium carbonate, a pH adjuster, to the mixture K to adjust the pH to 7. Filter the mixture first, then perform vacuum treatment. Evacuate the vacuum in the reactor to -70 kPa. Stir continuously at 250 rpm for 2 hours at room temperature to remove residual monomers and obtain an aqueous dispersion of the binder.

[0097] Based on the total mass of the monomers, the mass percentages of the first monomer (80.6%), the second monomer (17%), the crosslinking monomer (0.4%), and the functional monomer (2%) were as follows: the mass ratio of the total monomer mass to deionized water was 1:10; the mass ratio of the total monomer mass to the initiator was 1:0.06; and the mass ratio of the total monomer mass to the pH adjuster was 1:0.06. Based on the copolymer mass, the mass percentages of the first monomer unit (A), the second monomer unit (B), the crosslinking monomer unit (C), and the functional monomer unit (D) are shown in Table 2.

[0098] <Preparation of Negative Electrode Sheets>

[0099] Using deionized water as a solvent, the aqueous dispersion of the adhesive prepared above was formulated into an adhesive slurry with a solid content of 15%.

[0100] Silicon-carbon (Si:C = 50:50), graphite, and carboxymethyl cellulose dispersant were mixed. A binder slurry was first added and stirred until homogeneous. Then, deionized water was added as a solvent to prepare a slurry with a solid content of 45 wt%. After homogenization using a vacuum mixer, the slurry was obtained as the negative electrode slurry. This negative electrode slurry was uniformly coated onto one surface of a 6 μm thick copper foil used as a negative electrode current collector. The foil was then dried at 120°C to obtain a negative electrode sheet with a single-sided negative electrode material layer. The coating weight of the negative electrode material layer was 142 mg / 1540 mm². 2The above steps are then repeated on the other surface of the copper foil to obtain a negative electrode sheet with a double-sided coating of negative electrode material. After drying at 120℃ and cold pressing, the sheet is cut and tabs are welded to obtain a negative electrode sheet with dimensions of 78mm × 875mm for later use. The thickness of the single-sided negative electrode material layer is 54.5μm. Based on the mass of the negative electrode material layer, the silicon content of the silicon-containing material is 30%, the dispersant content is 0.5%, the binder content is 3%, and the balance is graphite.

[0101] <Preparation of the positive electrode>

[0102] LiCoO2 (positive electrode active material), Super P (positive electrode conductive agent), and polyvinylidene fluoride (PVDF) (positive electrode binder) were mixed in a mass ratio of 97.9:0.9:1.2. N-methylpyrrolidone (NMP) was added as a solvent to prepare a slurry with a solid content of 75 wt%. The mixture was then stirred uniformly under vacuum to obtain the positive electrode slurry. This positive electrode slurry was uniformly coated onto one surface of a 10 μm thick aluminum foil used as a positive electrode current collector. The foil was then dried at 120°C to obtain a positive electrode sheet with a single-sided coating of the positive electrode material layer. The coating weight of the positive electrode material layer was 267.8 mg / 1540 mm². 2 The above steps are then repeated on the other surface of the aluminum foil to obtain a positive electrode sheet with a double-sided coating of positive electrode material. After drying at 120℃, it is cold-pressed, then cut and welded with tabs to obtain a positive electrode sheet with a size of 74mm×867mm for later use. The thickness of the single-sided positive electrode material layer is 42μm.

[0103] <Preparation of Electrolyte>

[0104] In an environment with a water content of less than 10 ppm, ethylene carbonate (EC) and propylene carbonate (PC) were mixed at a mass ratio of 1:1 to obtain a non-aqueous solvent. Then, lithium salt LiPF6 was added to the non-aqueous solvent and mixed thoroughly to obtain the electrolyte. The lithium salt content was 12.5% ​​by mass, with the remainder being non-aqueous solvent.

[0105] <Septum>

[0106] A porous polyethylene film with a thickness of 7μm (provided by Celgard) was used as the separator.

[0107] <Preparation of Lithium-ion Batteries>

[0108] The prepared positive electrode, separator, and negative electrode are stacked sequentially, with the separator positioned between the positive and negative electrodes to provide insulation. The electrode assembly is then wound to obtain the electrode assembly. The electrode assembly is placed in an aluminum-plastic film packaging bag and dehydrated at 80°C. The electrolyte prepared above is then injected, and the battery undergoes vacuum sealing, settling, formation, degassing, and edge trimming to obtain a lithium-ion battery. The formation upper limit voltage is 4.15V, the formation temperature is 70°C, and the formation settling time is 2 hours.

[0109] Examples 1-2 to 1-23

[0110] Except for adjusting the relevant parameters according to Table 2, everything else is the same as in Example 1-1.

[0111] Examples 1-24 to Examples 1-27

[0112] Except for adjusting the time and / or temperature of the first reaction according to Table 1, so that the adhesive-related parameters are as shown in Table 2, the rest is the same as in Examples 1-1.

[0113] Examples 2-1 to 2-6

[0114] Except for adjusting the mass percentage of the binder according to Table 3, the rest is the same as in Examples 1-1. When the mass percentage of the binder changes, the mass percentages of the silicon-containing material and the dispersant remain unchanged, while the mass percentage of graphite changes accordingly.

[0115] Examples 2-7 to 2-8

[0116] Except for adjusting the mass percentage of silicon-containing materials to achieve the silicon mass percentage as shown in Table 3, the rest is the same as in Examples 1-1. When the mass percentage of silicon-containing materials changes, the mass percentages of binder and dispersant remain unchanged, while the mass percentage of graphite changes accordingly.

[0117] Comparative Examples 1 to 5

[0118] Except for adjusting the relevant parameters according to Table 2, everything else is the same as in Example 1-1.

[0119] Comparative Examples 6 to 7

[0120] Except for adjusting the time and temperature of the first reaction according to Table 1 so that the adhesive-related parameters are as shown in Table 2, the rest is the same as in Example 1-1.

[0121] The relevant parameters and performance tests of each embodiment and comparative example are shown in Tables 1 to 3.

[0122] Table 1

[0123] The first reaction temperature T1 (°C) First reaction time t1(h) Example 1-1 80 4 Examples 1-24 70 4 Examples 1-25 80 5 Examples 1-26 80 3 Examples 1-27 90 4 Comparative Example 6 95 4 Comparative Example 7 65 4

[0124] Table 2

[0125]

[0126]

[0127] Note: " / " in Table 2 indicates that there are no relevant parameters or substances.

[0128] As can be seen from Examples 1-1 to 1-27 and Comparative Examples 1 to 7, using copolymers formed by polymerizing the first monomer, the second monomer, the crosslinking monomer, and the functional monomer within the scope of this application as binders, and controlling the phase angle enhancement rate α% of the binder within the scope of this application, is beneficial for the binder to uniformly adhere to the surface of the negative electrode active material particles. When the binder of this application is applied to the negative electrode sheet, it enables the lithium-ion battery to have a high capacity retention rate and a low DCR, indicating that the lithium-ion battery has good cycle performance and kinetic performance. In the binders of Comparative Examples 1 to 5, the monomers forming the copolymer do not include at least one of the first monomer, the second monomer, the crosslinking monomer, and the functional monomer, and the phase angle enhancement rate α% is not within the scope of this application. The phase angle enhancement rate α% of the binders of Comparative Examples 6 to 7 is also not within the scope of this application. The lithium-ion batteries in these examples have a low capacity retention rate and a high DCR, indicating poor cycle performance and kinetic performance.

[0129] The phase angle enhancement rate α% of the binder typically affects the cycle performance and kinetic performance of lithium-ion batteries. As can be seen from Examples 1-1 to 1-27 and Comparative Examples 6 to 7, when the value of α is too large (e.g., in Comparative Example 6) and when the value of α is too small (e.g., in Comparative Example 7), the lithium-ion battery exhibits lower capacity retention and higher DCR, indicating poor cycle performance and kinetic performance. Therefore, by adjusting the value of α within the range specified in this application, the lithium-ion battery can achieve higher capacity retention and lower DCR, indicating good cycle performance and kinetic performance.

[0130] The phase angle θ0° of the binder typically affects the cycle performance and kinetic performance of lithium-ion batteries. As can be seen from Examples 1-1 to 1-27, adjusting the value of θ0 within the range of this application can result in lithium-ion batteries exhibiting high capacity retention and low DCR, indicating that lithium-ion batteries possess good cycle performance and kinetic performance.

[0131] The mass percentages of the first monomer unit (A), the second monomer unit (B), the crosslinked monomer unit (C), and the functional monomer unit (D) typically affect the cycle performance and kinetic performance of lithium-ion batteries. As can be seen from Examples 1-1 to 1-17, adjusting the values ​​of A, B, C, and D within the range of this application can result in lithium-ion batteries exhibiting high capacity retention and low DCR, indicating that the lithium-ion batteries possess good cycle performance and kinetic performance.

[0132] The types of the first monomer, second monomer, cross-linked monomer, and functional monomer typically affect the cycle performance and kinetic performance of lithium-ion batteries. As can be seen from Examples 1-1, 1-18 to 1-23, selecting the first monomer, second monomer, cross-linked monomer, and functional monomer within the scope of this application can result in lithium-ion batteries exhibiting high capacity retention and low DCR, indicating that lithium-ion batteries possess excellent cycle performance and kinetic performance.

[0133] The number of carbon atoms in the second monomer typically affects the cycle performance and kinetic performance of lithium-ion batteries. As can be seen from Examples 1-1, 1-19 to 1-21, adjusting the number of carbon atoms in the second monomer within the scope of this application can result in lithium-ion batteries exhibiting high capacity retention and low DCR, indicating that lithium-ion batteries possess good cycle performance and kinetic performance.

[0134] The mass ratio X of the functional cell and the second cell typically affects the cycle performance and kinetic performance of lithium-ion batteries. As can be seen from Examples 1-1 to 1-7 and Examples 1-14 to 1-17, adjusting the value of X within the range of this application can result in lithium-ion batteries exhibiting high capacity retention and low DCR, indicating that lithium-ion batteries have good cycle performance and kinetic performance.

[0135] The weight-average molecular weight of the copolymer, the swelling degree of the binder in the electrolyte, and the dissolution rate typically affect the cycle performance and kinetic performance of lithium-ion batteries. As can be seen from Examples 1-1 to 1-27, adjusting the above parameters within the scope of this application can result in lithium-ion batteries exhibiting high capacity retention and low DCR, indicating that lithium-ion batteries possess good cycle performance and kinetic performance.

[0136] Figure 1 The diagram shows the phase angle of the binder in Example 1-1 and the phase angle of the mixture of binder and negative electrode active material as a function of shear stress. Figure 1In the present application, the phase angle θ0° of the binder in Example 1-1 is 15.0° (the phase angle under shear stress of 0.1 Pa, the same below), the phase angle θ1° of the mixture of binder and negative electrode active material is 22.5°, and the phase angle enhancement rate α% of the binder is 50%. Figure 2 The graphs showing the phase angle of the binder in Comparative Example 1 and the phase angle of the mixture of binder and negative electrode active material as a function of shear stress are presented. Figure 2 In Comparative Example 5, the phase angle θ0° = 5.3° of the binder, and the phase angle θ1° = 5.8° of the mixture of binder and negative electrode active material, with a phase angle enhancement rate α% = 11.5%. The comparison shows that the binder in Examples 1-1 of this application has a higher phase angle enhancement rate.

[0137] Table 3

[0138]

[0139] Note: " / " in Table 3 indicates that there are no relevant parameters or substances.

[0140] The mass percentage content of the binder typically affects the cycle performance and kinetic performance of lithium-ion batteries. As can be seen from Examples 1-1, 2-1 to 2-6, adjusting the mass percentage content of the binder within the scope of this application can result in lithium-ion batteries exhibiting high capacity retention and low DCR, indicating that the lithium-ion batteries possess good cycle performance and kinetic performance.

[0141] The mass percentage of silicon typically affects the cycle performance and kinetic performance of lithium-ion batteries. As can be seen from Examples 1-1, 2-7 to 2-8, adjusting the mass percentage of silicon within the scope of this application can result in lithium-ion batteries exhibiting high capacity retention and low DCR, indicating that the lithium-ion batteries possess good cycle performance and kinetic performance.

[0142] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, or article that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, or article.

[0143] The various embodiments in this specification are described in a related manner. The same or similar parts between the various embodiments can be referred to each other. Each embodiment focuses on describing the differences from other embodiments.

[0144] The above description is only a preferred embodiment of this application and is not intended to limit this application. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the scope of protection of this application.

Claims

1. A binder for a negative electrode sheet, wherein, The adhesive comprises a copolymer, wherein the monomers forming the copolymer include a first monomer, a second monomer, a crosslinking monomer, and a functional monomer, wherein the first monomer includes at least one of acrylic acid or methacrylic acid, and the second monomer is selected from C7 to C6. 19 Acrylic ester compounds, wherein the functional monomer comprises at least one of allyltriethoxysilane, N-propyltriethoxysilane or 3-aminopropyltriethoxysilane; The phase angle enhancement rate of the adhesive is α%, 25≤α≤75; Under the conditions of an ambient temperature of 25±5℃, a shear stress of 0.1Pa, and an applied shear stress frequency of 1Hz, the phase angle of the binder is θ0°, the phase angle of the mixture of the binder and the negative electrode active material is θ1°, and the mass ratio of the binder to the negative electrode active material in the mixture is 7:

3.

2. The adhesive according to claim 1, wherein, 40≤α≤60。 3. The adhesive according to claim 1, wherein, 12≤θ0≤18.

4. The adhesive according to claim 1, wherein, The crosslinking monomer includes at least one of pentaerythritol allyl ether, trimethylolpropane triacrylate, divinylbenzene, ethoxylated trimethylolpropane triacrylate, or pentaerythritol triallyl ether.

5. The adhesive according to claim 1, wherein, The first monomer, the second monomer, the crosslinking monomer, and the functional monomer respectively constitute the first monomer unit, the second monomer unit, the crosslinking monomer unit, and the functional monomer unit of the copolymer. Based on the mass of the copolymer, the first monomer unit has a mass percentage content of 67.6% to 87.6%, the second monomer unit has a mass percentage content of 10% to 30%, the crosslinking monomer unit has a mass percentage content of 0.2% to 1%, and the functional monomer unit has a mass percentage content of 1% to 3%.

6. The adhesive according to claim 5, wherein, Based on the mass of the copolymer, the second monomer unit has a mass percentage content of 15% to 20%, and the crosslinking monomer unit has a mass percentage content of 0.3% to 0.5%; and / or, The mass ratio X of the functional unit and the second unit is 0.06 to 0.

2.

7. The adhesive according to claim 1, wherein, The second monomer is selected from C 10 To C 12 Acrylic ester compounds.

8. The adhesive according to claim 1, wherein, The second monomer includes at least one of butyl acrylate, isooctyl acrylate, butyl methacrylate, lauryl methacrylate, hexadecyl acrylate, or lauryl acrylate.

9. The adhesive according to any one of claims 1 to 8, wherein, The copolymer has a weight-average molecular weight (Mw) of 50,000 g / mol to 100,000 g / mol.

10. The adhesive according to any one of claims 1 to 8, wherein, The adhesive has a swelling degree of 10% to 30% in the electrolyte, and / or the adhesive has a dissolution rate of 2% to 3% in the electrolyte.

11. A secondary battery comprising a positive electrode and a negative electrode, the negative electrode comprising a negative current collector and a negative electrode material layer disposed on at least one surface of the negative current collector, the negative electrode material layer comprising the binder according to any one of claims 1 to 10.

12. The secondary battery according to claim 11, wherein, The negative electrode material layer includes a negative electrode active material, which includes graphite and silicon-containing materials. Based on the mass of the negative electrode material layer, the mass percentage of silicon element is 1.5% to 30%.

13. The secondary battery according to claim 11, wherein, Based on the mass of the negative electrode material layer, the binder has a mass percentage content of 1% to 10%.

14. The secondary battery according to claim 11, wherein, Based on the mass of the negative electrode material layer, the binder has a mass percentage content of 2% to 5%.

15. An electronic device comprising a secondary battery as claimed in any one of claims 11 to 14.

Citation Information

Patent Citations

  • Secondary battery and electronic device

    CN118507844A

  • Low refractive index particles

    WO2014064427A1